Monitoring single-heteroatom loss during deoxygenation and denitrogenation of soluble organic matter in coal using mass spectrometric methods. (15th May 2021) - Fan, Xing; Dong, Xueming; Wei, Wen-Han; Gao, Zhen-Yu; Bai, Hong-Cun; Mo, Wen-Long
Highlights: Monitoring catalytic conversion of coal using mass spectrometry. Single-heteroatom loss method well fits denitrogenation patterns. Aromatic cores of compounds between 300 and 400 Da show similarity in ring size. Abstract: The structure-reactivity relationship during catalytic reactions for coal has been extensively simulated by using model compounds. However, the direct study of structure-reactivity relationship is not sufficient for coal, the complex mixture, partially due to the challenging task of monitoring catalytic reactions in complex mixtures at the molecular level. In this study, a tandem mass spectrometry (MS) approach was designed for selective observation of catalytic single-atom denitrogenation and deoxygenation reactions of a coal. According to the tandem MS data, structure of aromatic cores, total carbon number in alkyl chains, heteroatom release efficiency and preference of heteroatom removal on aromatic cores versus alkyl chains were explored and compared to reveal the relationship between heteroatom release pattern and molecular structure. Structure-reactivity relationship was not clearly observed in deoxygenation patterns due to majorities of molecules contain multiple oxygen atoms. However, structure-reactivity relationships were revealed in denitrogenation patterns due to the presence of single nitrogen atom in most nitrogen-containing molecules.